Correlation of fetal ventricular size and need for postnatal cerebrospinal fluid diversion surgery in open spina bifida. (1st June 2022) - Agrawal, S.; Al‐Refai, A.; Abbasi, N.; Kulkarni, A. V.; Pruthi, V.; Drake, J.; Ryan, G.; Van Mieghem, T.
ABSTRACT: Objectives: Open spina bifida is a common cause of hydrocephalus in the postnatal period. In‐utero closure of the fetal spinal defect decreases the need for postnatal cerebrospinal fluid (CSF) diversion surgery. Good prenatal predictors of the need for postnatal CSF diversion surgery are currently lacking. In this study, we aimed to assess the association of fetal ventriculomegaly and its progression over the course of pregnancy with the rate of postnatal hydrocephalus requiring intervention. Methods: In this retrospective study, fetuses with a prenatal diagnosis of open spina bifida were assessed longitudinally. Ventricular diameter, as well as other potential predictors of the need for postnatal CSF diversion surgery, were compared between fetuses undergoing prenatal closure and those undergoing postnatal repair. Results: The diameter of the lateral ventricle increased significantly throughout gestation in both groups, but there was no difference in maximum ventricular diameter at first or last assessment between fetuses undergoing prenatal closure and those undergoing postnatal repair. There was no significant difference in the rate of progression of ventriculomegaly between the two groups, with a mean progression rate of 0.83 ± 0.5 mm/week in the prenatal‐repair group and 0.6 ± 0.6 mm/week in the postnatal‐repair group ( P  = 0.098). Fetal repair of open spina bifida was associated with a lower rate of postnatal CSF diversion surgery ( P  < 0.001). In all subjects, regardless of whether they had prenatal or postnatal surgery, the severity of ventriculomegaly at first and last assessments was associated independently with the need for postnatal CSF diversion surgery ( P  = 0.005 and P  = 0.001, respectively), with a greater need for surgery in fetuses with larger ventricular size, even after controlling for gestational age at assessment. Conclusions: In fetuses with open spina bifida, fetal ventricular size increases regardless of whether spina bifida closure is performed prenatally or postnatally, but the need for CSF diversion surgery is significantly lower in those undergoing prenatal repair. Ventriculomegaly is associated independently with the need for postnatal CSF diversion in fetuses with open spina bifida, irrespective of timing of closure. © 2021 International Society of Ultrasound in Obstetrics and Gynecology.